2065. Increasing the HIV screening rates in Rural Syringes Service Programs. (15th December 2022) - Collins, Jana; Soria, Jaime; Thacker, James; Corby-Lee, Greg; White, Connie; Johnson, Tisha; Hoven, Ardis; Thornton, Alice C
Abstract: Background: The Kentucky Income Reinvestment Program (KIRP) is a statewide reinvestment of income generated by the Ryan White HIV/AIDS Program (RWHAP) Kentucky AIDS Drug Assistance Program, which provides comprehensive early intervention services targeting those at the highest risk for HIV infection. The objective of this study was to compare the HIV screening rates in persons who inject drugs (PWID) at Syringe Service Programs (SSP) supported by KIRP versus SSPs not supported by KIRP in Kentucky Methods: A cross-sectional study was conducted on 54 SSPs. We compared the HIV screening rates in the first quarter of 2020, 2021, and 2022. Fisher's exact test compared the HIV screening rates between the KIRP supported SSPs (KSSP) versus Non-KIRP supported SSPs (NKSSP). Study data were collected and managed using REDCap electronic data capture tools hosted at Kentucky Department for Public Health. The statistical analyses were performed with Stata 17 (College Station, TX: Stata Corp LLC). Results: The analysis included data of 21, 072 PWID who attended the SSPs utilizing the REDCap electronic data capture tool during the study timeframe. In the first quarter of 2022, a total of 1, 607/4795 (33.5%) PWID were screened for HIV at KSSP vs 12/482 (2.5%) at NKSSP (p=< 0.001). The difference in the screening rates has increased over the years since the KIRP began in 2019 (Figure 1). Conclusion: The HIV screening rate in PWID has increased significantly in the SSPs supported by KIRP through RWHAP program income early intervention funds. This increase has occurred mainly in rural counties where people who inject drugs remain a significant population at risk for new HIV infections. Disclosures: All Authors : No reported disclosures.